Rekonstruksi Hukum Keselamatan dan Kesehatan Kerja di Indonesia Pasca Reformasi Ketenagakerjaan: Analisis Disharmonisasi Regulasi dan Harmonisasi dengan Standar International Labour Organization - erie failenggo (Jurnal Hukum Lex Generalis, 2026)
Indonesia has numerous Occupational Safety and Health (OSH) regulations dispersed across various sectoral laws, resulting in regulatory inconsistencies, overlapping authorities and inefficiencies in implementation and enforcement. Moreover, the national OSH framework, primarily based on Law No. 1 of 1970 on Work Safety, has not fully adapted to contemporary workplace transformations such as digitalization, automation, the gig economy, platform work and remote working. This study aims to examine regulatory disharmonization within Indonesia’s OSH legal system and to propose a reconstruction of OSH law aligned with International Labour Organization (ILO) standards. Using a normative legal research method with statutory, conceptual and comparative approaches, the study finds that fragmented regulations and the absence of an integrated OSH framework are the main challenges. Therefore, legal reconstruction is necessary through the development of a comprehensive riskbased framework, the strengthening of OSH culture, the harmonization of supervisory authority and the ratification of ILO Conventions No. 155 (1981) and No. 187 (2006) to establish a modern, responsive and prevention-oriented national OSH system.